Thermodynamic assessment of the Co-Mg binary system - Yang L.-F.; Si X-D.; Zhang H.-D.; Gao F.-G.; Zeng Y.-P.; Liu Y.-L.; Wang Y.; Du Y. (Journal of Mining and Metallurgy. Section B: Metallurgy)
No thermodynamic description was performed for the Co-Mg binary system according to literature review. Consequently, this binary system has been investigated by means of CALPHAD (CALculation of PHAse Diagrams) approach in the present work. The experimental phase diagram and thermodynamic data available in the literature were critically assessed. Based on the reliable literature data, a new set of self-consistent thermodynamic parameters for the Co-Mg system is obtained. The calculated results agree well with the experimental data from the literature, indicating the reasonability of the present thermodynamic optimization.